(untitled) (Research, Society and Development, 2022)
Objective: the present study aims to evidence the most recurrent muscle injury techniques in the literature. Methodology: This is a bibliographical research of the integrative review type of literature. The articles were searched in 2021, from November 22 to 24, in the PubMed database, using the eligibility criteria. Results and Discussion: According to the search strategy used in this study, of all articles only 28 studies met the eligibility criteria. When analyzing the publication journals, it was observed that the most recurrent were PLoS One (7.14%), Int J Med Sci (7.14%), and J Trauma Acute Care with (7.14%). It was also evidenced that the number of publications on the subject has been growing over the years, when it compared the year 2016 (10.71%) with later years, except in 2019 with the same percentage of 10.71% and 2021 with zero publication. The breeds most used in the experiments were Sprague-Dawley (32.14%) and Wistar with 25%. There was a predominance of models due to contusion (35.71%), followed by excessive use injury (10.71%), and traumatic injury (10.71%), for induction of muscle injury in rodents. Conclusion: According to the results of this review, the most recurrent muscle injury induction models were injury by contusion, followed by excessive use injury, and traumatic injury. However, all the techniques addressed in the present study were able to reproduce with excellence the mechanism of muscle injury.